Pharmacological properties of Humulus scandens: Insights from the TCMSP database and existing understanding - De Xin Dang; Desheng Li; Shi Qi Xu; Feng He; Xinhua Xia; Shaoyong Xu (Pharmacological Research - Modern Chinese Medicine)
Introduction: Humulus scandens (HS) has been traditionally used in folk medicine for treating a wide spectrum of ailments. Despite its long history of use, its integration into modern medicine has been relatively limited. This review aims to summarize the existing understanding of the pharmacological effects of HS and explore its potential pharmacological benefits using the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database. Methods: we reviewed the pharmacological effects of HS by conducting a thorough literature search across databases like Google Scholar, CNKI, RISS, and J-Stage, as well as searching classical sources such as “Ben Cao Gang Mu” and “Ming Yi Bie Lu”. Furthermore, we used the TCMSP database to identify bioactive components of HS, focusing on those with oral bioavailability ≥ 30 % and drug-likeness ≥ 0.18, and explored the potential diseases associated with these components. Results: HS as a traditional herbal medicine has been used to treat congestion, hematuria, strangury, watery diarrhea, and sores, as well as to enhance kidney function and promote urination. It has also served as a remedy for snake and scorpion bites. Modern experimental evidence suggests that HS exhibits efficacy in treating a wide range of conditions, including inflammation, and disorders of the respiratory system, urinary system, skin, gastrointestinal tract, nervous system, and cardiocerebral vascular system, as well as immunity-related diseases. Furthermore, it demonstrates promising properties in anti-cancer activity, hepatoprotection, lipid metabolism regulation, pain relief, alleviating diarrhea, and treating mental illness. Beyond these known effects, evidence from the TCMSP database highlights its potential in treating tumors, eye disorders, muscle disorders, diabetes, insomnia, and developmental disabilities. Discussion: HS is a traditional herbal medicine with multiple pharmacological properties. However, while some pharmacological properties of HS have been validated through experiments, further research efforts are needed to explore its other effects. Such endeavors are crucial for a thorough understanding of HS and its potential therapeutic application.